The Cotton cleaning technology : INCREASING THE EFFICIENCY OF RETAINING DEVICE FOR FINE AND LARGE HEAVY MIXTURES IN COTTON RAW MATERIALS - Rayimjonov, Mirzavali; Rahimov , Fayzullo; Sarimsakov , Akramjon; Muradov , Ru (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Conclusion.The proposed device is mainly to ensure that the seeded cotton raw material in cotton gins does not harm the seeded cotton when all kinds of heavy impurities get mixed with the cotton due to machine and hand picking and negligence by the workers. The purpose of obtaining high-quality fiber and seed is put forward that it effectively carries out the process of trapping heavy impurities in its content. It consists in protecting the seed cotton from damage by passing it through less equipment. The device we offer consists of two-pocket and two-chamber surfaces, and the plates inside the pockets, which expel heavy impurities, are automatically opened and closed to prevent air ingress. Keeping control in our own hands by streaming to smartphones and computers ensures that this device efficiently removes heavy impurities. At the same time, in order to prevent the accumulation of raw cotton in many cases, especially when touching its vertical surface, there is a spring in the bottom part of the iron plate installed at a 30-degree slope, which helps to facilitate the damage and spread of the accumulated cotton, and then transfer it to the next parts. will give. In conclusion, it can be said that this device consists in increasing the efficiency of the processes of trapping small and large heavy impurities in raw cotton and using artificial intelligence without the automatic human factor.